PENGARUH PRODUCT QUALITY, BRAND IMAGE, PROMOTION, DAN WORD OF MOUTH TERHADAP CUSTOMER SATISFACTION MELALUI PURCHASE DECISION SEBAGAI VARIABEL INTERVENING PADA USAHA RENGGINANG MAK LIA DI TANJUNG GLUGUR SITUBONDO - Riko Ramdani; Rini Kartika Sari; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This research was conducted to examine the influence of Product Quality, Brand Image, Promotion, and Word of Mouth on Customer Satisfaction through Purchase Decision as an intervening variable at Rengginang Mak Lia in Tanjung Glugur, Situbondo. The study employed a purposive sampling method under the non-probability sampling technique, involving 110 respondents. Data processing and analysis were carried out using SmartPLS 3.0. Several analytical procedures were applied, including convergent validity, reliability, classical assumption, goodness of fit (GOF), coefficient of determination, inner model analysis, and hypothesis testing. The findings from the direct effect analysis indicated that Product Quality and Word of Mouth did not significantly affect Purchase Decision. On the other hand, Brand Image and Promotion significantly influenced Purchase Decision. In addition, Product Quality, Brand Image, Promotion, and Purchase Decision were not found to significantly influence Customer Satisfaction. However, Word of Mouth showed a significant impact on Customer Satisfaction. Furthermore, the indirect effect analysis demonstrated that Product Quality, Brand Image, Promotion, and Word of Mouth did not significantly influence Customer Satisfaction through Purchase Decision as the mediating variable.